Implementasi Algoritma Triple Exponansial Smooting Untuk Prediksi Persediaan Obat - Dona Roni Tambunan; Muhammad Syahrizal; Saidi Ramadan Siregar (Journal of Computer System and Informatics (JoSYC), 2020)
According to Permenkes 017 / menkes / per / x / 1993, drugs are alloys that are ready to be used to influence or examine physiology or pathology in determining the diagnosis, prevention, healing, recovery, improvement of health and contraception. This research intends to predict the supply of drugs. The method used in this research is triple exponential smoothing. The data used in this study are data from 2013 to 2018. The results of this study are prediction of drug inventory. Prediction is a process of estimating systematically about something that is most likely to occur in the future based on past and present information that is owned, so that errors (the difference between something that happens and the estimated results) can be minimized. Prediction does not have to provide a definite answer to events that will occur, but rather try to find answers as close as possible to what will happen. The benefit of this research is to be able to predict the availability of drugs so that they can find out the amount of drug supplies each year at the RSU Yoshua Lubuk Pakam